Alterações estruturais do solo e perdas de produtividade na cultura do milho - SILVA, Fagner Luiz Rodrigues; GUIMARÃES JUNNYOR, Wellingthon da Silva; VENDRUSCOLO, Eduardo Pradi; FERREIRA, Laura Martins; RODRIGUES, Gustavo Sanches; ALVES, Vitória Carolina Dantas (ANAIS DO ENIC, 2023)
-